THE EFFECT OF MONSOON PHENOMENON ON DRY RUBBER PRODUCTIVITY IN SUMATERA AND JAVA - Vaiqoturrokhmah
Rainfall in Indonesia is influenced by the monsoon which is driven by the presence of high-pressure cells on the Asian continent and low-pressure cells on the Australian continent alternately. The increase and decrease in rainfall doe to monsoon has an impact on the plantation sector, one of which is the productivity of dry rubber in Indonesia. Therefore, it is important to know the influence of monsoon on the productivity of dry rubber. The purpose of this study was to see the effect of monsoon phenomena on the productivity of dry rubber in Sumatra and Java with the study points of North Sumatra, Riau, South Sumatra, West Java, and East Java, using monthly rainfall data from the Meteorology, Climatology, and Geophysics agency (BMKG), AUSMI index data is zonal wind data from the IRI Data Library (IRIDL), as well as monthly dry rubber productivity data sourced from the Central Statistics Agency (BPS) since 2006-2019. Fast Fourier Transform (FFT), and Butterworth Bandpass Filter is a method used to see the response of monsoon phenomena to rainfall and its effect on dry rubber productivity in the study area. The monsoon phenomenon has a different effect on rainfall in each study area. Rainfall in Riau, South Sumatra, West Java, and East Java is strong with the influence of monsoon, confirmed by a correlation value of 0.5 to 0.7. The highest correlation between rainfall and productivity was found in lag 1 for North Sumatra and Riau with 0.487 and 0.231, and lag 2 for South Sumatra, West Java, and East Java with 0.163, 0.273, and 0.323. The effect of increasing and decreasing rainfall on seasonal increase and decrease in productivity was not consistent for all study areas. The monsoon phenomenon does not directly affect productivity but rather monsoon-influenced rainfall that directly affects the productivity of dry rubber.